Belief Reasoning and Emotion Understanding in Balanced Bilingual and Language-Dominant Mexican American Young Children. Issue 2 (3rd March 2016) - Weimer, Amy A.; Gasquoine, Philip G.
ABSTRACT: Belief reasoning and emotion understanding were measured among 102 Mexican American bilingual children ranging from 4 to 7 years old. All children were tested in English and Spanish after ensuring minimum comprehension in each language. Belief reasoning was assessed using 2 false and 1 true belief tasks. Emotion understanding was measured using subtests from the Test for Emotion Comprehension. The influence of family background variables of yearly income, parental education level, and number of siblings on combined Spanish and English vocabulary, belief reasoning, and emotion understanding was assessed by regression analyses. Age and emotion understanding predicted belief reasoning. Vocabulary and belief reasoning predicted emotion understanding. When the sample was divided into language-dominant and balanced bilingual groups on the basis of language proficiency difference scores, there were no significant differences on belief reasoning or emotion understanding. Language groups were demographically similar with regard to child age, parental educational level, and family income. Results suggest Mexican American language-dominant and balanced bilinguals develop belief reasoning and emotion understanding similarly.